The role of affective interest in vocational interest measurement - Onder, Casey C., author; Dik, Bryan, advisor; Byrne, Zinta, committee member; Feller, Rich, committee member (Colorado State University. Libraries, 2012)
Most vocational interest inventories used today operationalize interests in terms of enjoyment or liking. The potential role of affective interest in vocational preferences has not been examined empirically, despite indications that affective interest and enjoyment are distinct as emotions. The present study aimed to extend research distinguishing affective interest from enjoyment to the context of vocational preferences, and to determine whether incorporating affective interest items into an enjoyment-based vocational interest measure would improve its criterion-related validity for academic major choice and satisfaction. 423 university undergraduates completed online survey items rating vocational activities on various dimensions, including enjoyment and interest, and indicated their academic majors and major satisfaction. Results regarding the discriminant validity of enjoyment and interest in vocational activities were mixed. Affective interest did not have incremental criterion-related validity for academic major choice and satisfaction. These findings and the study's limitations suggest the need for further research on the potential role of affective interest in vocational interest measurement.
Keywords: career counseling; construct validity; emotion; measurement; vocational interests; vocational psychology